2019
DOI: 10.1002/hed.25613
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet light‐related DNA damage mutation signature distinguishes cutaneous from mucosal or other origin for head and neck squamous cell carcinoma of unknown primary site

Abstract: Background Head and neck squamous cell carcinoma of unknown primary site (HNSCCUP) is a diagnostic challenge. Identification of an ultraviolet (UV) light‐related DNA damage signature using next‐generation sequencing (NGS) can classify the primary site of origin as cutaneous. Methods A 62‐year‐old male was seen with 2 months of left neck swelling. He was a lifetime nonsmoker but had a history of cutaneous squamous cell carcinoma (SCC) of the left helix. He was also found to have left hilar adenopathy. He had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…[29][30][31] This finding is much lower compared with cSCCs, which are reported to be mutated in up to 75% of cases. 32 The impact of UV radiations is reasonably more applicable to periungueal/lateral nail fold SCCs, as in our series, compared with nail bed SCCs due to more direct sun exposure. However, it is not possible to totally exclude the role of UV, also in other localizations, as it was suggested that the nail plate may even be considered a convex lens favouring UV exposure.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…[29][30][31] This finding is much lower compared with cSCCs, which are reported to be mutated in up to 75% of cases. 32 The impact of UV radiations is reasonably more applicable to periungueal/lateral nail fold SCCs, as in our series, compared with nail bed SCCs due to more direct sun exposure. However, it is not possible to totally exclude the role of UV, also in other localizations, as it was suggested that the nail plate may even be considered a convex lens favouring UV exposure.…”
Section: Discussionsupporting
confidence: 52%
“…UV‐signature mutations (C>T transitions at dipyrimidine sites) were observed in our series in 4/20 cases and specifically all of them arising on the lateral nail fold (Figure 1). 29–31 This finding is much lower compared with cSCCs, which are reported to be mutated in up to 75% of cases 32 . The impact of UV radiations is reasonably more applicable to periungueal/lateral nail fold SCCs, as in our series, compared with nail bed SCCs due to more direct sun exposure.…”
Section: Discussionmentioning
confidence: 47%
“…For example, cutaneous squamous cell carcinoma (cSCC) possesses a high TMB (50 mutations per megabase DNA pairs) (42), leading to a high RR for cemiplimab [47% (95%CI, 34–61%)] (43). In addition, since an ultraviolet (UV) damage subclass of SCC and sebaceous carcinoma harbors a high somatic mutation burden with >50 mutations per megabase, UV damage signatures in TMB in these skin cancers could be predictive biomarkers for ICI treatment (44, 45). In melanoma, Madore et al reported that a lower non-synonymous mutation burden correlated with negative results for PD-L1 expression on melanoma cells, and significantly worse melanoma-specific survival in stage III melanoma (HR = 0.28; 95%CI, 0.12-0.66; P = 0.002) (3).…”
Section: Msi and Tmbmentioning
confidence: 99%
“…Once histopathological tissue is available from the lymph nodes, new clinically available technologies for "Next Generation Sequencing" (NGS), i.e. genetic profiling of (DNA) sequences, can be obtained, and can produce gene profiles associated with ultraviolet light damage which are more consistent with skin cancer, or conversely, profiles consistent with upper aerodigestive tract cancer (73). This knowledge may affect decisions regarding irradiation of the upper aerodigestive tract or the contralateral side of the neck postoperatively.…”
Section: Advanced Pathological and Molecular Diagnosis For Identifyinmentioning
confidence: 99%
“…Ultimately sequences for HPV-related mutations, EBV-related mutations, thyroid cancer associated molecular profiles, etc. could all prove useful (73).…”
Section: Advanced Pathological and Molecular Diagnosis For Identifyinmentioning
confidence: 99%